Pengaruh Kualitas Udara Terhadap Tingkat Kesehatan di Indonesia - Citra zahra; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to examine the effect of air quality on public health in Indonesia in both the short and long run. Public health is proxied by life expectancy at birth, while air quality is measured using PM2.5 concentration, with GDP per capita included as a control variable. The study employs annual time series data from 1992 to 2021 obtained from the World Bank. The Autoregressive Distributed Lag (ARDL) approach is applied to estimate both short-run dynamics and long-run relationships among variables. The results indicate the presence of cointegration among the variables. In the short run, air quality does not have a significant effect on life expectancy. However, in the long run, PM2.5 has a negative and statistically significant impact on public health. Meanwhile, GDP per capita shows a positive but insignificant effect in the long run. The Error Correction Model also confirms the existence of an adjustment mechanism toward long-run equilibrium. These findings suggest that the impact of air pollution on health is cumulative and requires sustained air quality management policies.